2008
DOI: 10.1007/s10461-007-9354-0
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Risk of HIV infection among Men Who Have Sex with Men

Abstract: In the United States, men who have sex with men (MSM) currently represent more than 50% of those living with HIV and over 70% of HIV+ men (CDC 2007, http://www.cdc.gov/hiv/topics/msm/resources/factsheets/pdf/msm.pdf ). Male-to-male sexual contact has been identified as the predominant route of transmission among this sub-group, which underscores the need for research that targets risk factors associated with risky sex-related HIV acquisition. Along these lines, research has shown that one potentially important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
156
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(175 citation statements)
references
References 62 publications
16
156
1
2
Order By: Relevance
“…Indeed, Kashubeck-West & Szymanski [1] reported that vaginal intercourse in their sample of predominantly gay men was "extremely infrequent." Similar to previous research in SMM [25][26][27], use of alcohol and/or drugs before or during sex was frequently reported in the current sample.…”
Section: Sex Actssupporting
confidence: 88%
“…Indeed, Kashubeck-West & Szymanski [1] reported that vaginal intercourse in their sample of predominantly gay men was "extremely infrequent." Similar to previous research in SMM [25][26][27], use of alcohol and/or drugs before or during sex was frequently reported in the current sample.…”
Section: Sex Actssupporting
confidence: 88%
“…This association may have resulted, in part, from the causal impact of acute alcohol use on sexual decision‐making 107, resulting in condomless sex 105, 108, 109, 110, 111, 112, 113, 114. Alternatively, other variables could be causally responsible for the associations between alcohol use and HIV/AIDS, especially the effect of risk‐taking behaviours and other personality traits 96, 115.…”
Section: Resultsmentioning
confidence: 99%
“…However, MSM who did not use alcohol during sex and those who were not depressed were more likely to engage in less risky sexual behaviors, consistent with prior studies. 10,[13][14][15]23 These findings suggest that HIV prevention interventions with MSM would benefit from addressing ''syndemics'' 24,25 associated with sexual risk taking. In particular, alcohol use, depression, and sexual risk behavior may be interacting health conditions that additively increase negative health consequences (i.e., HIV transmission) among some MSM.…”
Section: Discussionmentioning
confidence: 95%